Aortic dissection in a young male with isolated interrupted aortic arch: an unusual association - Shekhar Kunal; Pooja Pathak; Shruti Mittal; Vijay Pathak; Prateek Vaswani (Monaldi Archives for Chest Disease, 2021)
Interruption of the aortic arch (IAA) is a rare congenital anomaly which has been infrequently documented in the adult population. Aortic dissection (AD) is an emergency often presenting as acute chest pain and warranting urgent intervention. A 32-year-old male presented to Emergency Department with acute chest pain. Clinical examination revealed feeble pulses in bilateral lower limbs with a blood pressure difference between upper and lower limbs. Two-dimensional Echocardiography was suggestive of IAA with AD in the descending thoracic aorta. This was confirmed on computed tomography scan of the aorta which revealed complete interruption of the aortic arch distal to left subclavian artery along with the presence of an intimo-medial flap in descending thoracic aorta. A diagnosis of IAA with AD was made. The patient underwent an urgent aortic repair surgery following which he has been largely asymptomatic. A suspicion of AD should always be made in any patient presenting with acute onset chest pain radiating to the back along with accelerated hypertension/feeble pulses in extremity. Occurrence of AD in an adult with IAA is a distinct rarity and has been documented only thrice.